Rate of progression of cognitive decline in Alzheimer's disease: effect of butyrylcholinesterase K gene variation. - Holmes, C; Ballard, C; Lehmann, D; David Smith, A; Beaumont, H; Day, I; Nadeem Khan, M; Lovestone, S; McCulley, M; Morris, C; Munoz, D; O'Brien, K; et al. (2005)
OBJECTIVE: To determine whether individuals with Alzheimer's disease (AD) and the K variant allele of butyrylcholinesterase have a slower rate of cognitive decline than those without the K variant allele of butyrylcholinesterase. METHOD: The cognitive status of 339 community based subjects with AD was assessed with the Mini Mental State Examination at baseline and yearly over a three year follow up period. The rates of cognitive decline of subjects with and without the K variant allele were compared. RESULT: Presence of the K allele was associated with a slower average rate of cognitive decline in subjects with severe AD. CONCLUSIONS: This finding is consistent with the suggestion that the K variant of butyrylcholinesterase has an important role in disease progression in AD, and this may have implications for treatment.